2009
DOI: 10.1080/00016340902846080
|View full text |Cite
|
Sign up to set email alerts
|

Reduced bone mineral density in adult women diagnosed with menstrual disorders during adolescence

Abstract: This clinical follow-up study has demonstrated a high frequency of osteopenia in women diagnosed with menstrual disorders in adolescence. Previous anorectic behavior was the strongest negative predictor of BMD. It is important to pay attention to an underlying eating disorder in young women with menstrual dysfunction in order to promote bone health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…An evaluation of long-term (negative) effects on BMD in 87 women diagnosed with menstrual disorders during adolescence revealed a restrictive eating disorder at follow-up (six years after initial assessment) as the strongest predictor of low BMD, whereas a BMI > 22 and high physical activity appeared to be the most important counter-indicators [32]. Particularly with regard to bed rest, a pilot study on patients aged 13-21 years showed that limitation of physical activity during hospitalization for patients with AN is associated with suppressed bone formation and resorption and an imbalance in bone turnover [61].…”
Section: Discussionmentioning
confidence: 99%
“…An evaluation of long-term (negative) effects on BMD in 87 women diagnosed with menstrual disorders during adolescence revealed a restrictive eating disorder at follow-up (six years after initial assessment) as the strongest predictor of low BMD, whereas a BMI > 22 and high physical activity appeared to be the most important counter-indicators [32]. Particularly with regard to bed rest, a pilot study on patients aged 13-21 years showed that limitation of physical activity during hospitalization for patients with AN is associated with suppressed bone formation and resorption and an imbalance in bone turnover [61].…”
Section: Discussionmentioning
confidence: 99%
“…Adolescence is a particularly critical time for developing anorexia nervosa, and BMD is lower in women developing anorexia nervosa during adolescence compared with those who develop this in adulthood, even when the duration of amenorrhea is comparable [4]. Recent studies corroborate these data and indicate that adult women with a history of menstrual dysfunction and restrictive eating disorders in adolescence have a high prevalence of low BMD [5]. These data speak to the permanent effects anorexia nervosa can have on adult bone mass throughout life, even if there is recovery.…”
Section: Impact Of Anorexia Nervosa On Bone Metabolismmentioning
confidence: 99%
“…In other words, weight may be maintained or gained on fewer calories than would otherwise be expected. This can make it difficult for athletes to achieve optimal body composition while loss of menses puts the individual at risk of developing significant health problems, particularly loss of bone mineral density (BMD) (Beals & Hill, 2006;Manore et al, 2007;Wiksten-Almströmer et al, 2009).…”
Section: Body Compositionmentioning
confidence: 99%